Innovative research of plasma physics for life sciences - D. Boonyawan (2018)
© Published under licence by IOP Publishing Ltd. In medicine, cold atmospheric plasma (CAP) for the medical treatment is a new field in plasma application, called plasma medicine. CAP contains mix of excited atoms and molecules, UV photons, charged particles as well as reactive oxygen species (ROS) and reactive nitrogen species (RNS). Typical species in air-CAPs are O 3 , OH, N x O x , and HNO x . The current developments in this field have fuelled the hope that CAP could be an interesting new therapeutic approach in the treatment of cancer. CAP apparently demonstrated effect on cancer cell apoptosis which did not induce cell necrosis or disruption. Moreover, CAP seemed to be selective for cancer cells since it was more effective in tumor cells than in normal non-neoplastic cells. In bioscience, dentistry and veterinary medicine : Since CAP, is delivered at room temperature, which results in less damaging effects on living tissue, while still has the efficiency in disinfection and sterilization. Recent studies proved that it is able to inactivate gram-negative and gram-positive bacteria, fungi, virus, spore, various parasites, and foreign organisms or pathogens without harming tissue. Moreover, cold plasma has been used effectively in medical field such as dental use, inducing apoptosis of malignant cells, stopping bleeding, promoting wound healing and tissue regeneration. Sericin hydrolysates, originating from silkworm is found support cell proliferation, expand cell adhesion and increase cell yield. The covalent linkage between a bioactive protein molecule and polystyrene dish surface via a carbon intermediate layer can slow down the release rate of protein compound into the phosphate buffer saline (PBS) solution. We found that a-C films and a-C:N 2 films show good attachment of human bone marrow-derived mesenchymal stem cells (hBM-MSCs). All of carbon modified-Polystyrene(PS) dishes revealed the less release rate of sericin molecules into PBS solution than PS control.